Pengaruh Media Video Edukasi Terhadap Pengetahuan Dan Sikap Ibu Hamil Tentang 1000 HPK (Hari Pertama Kehidupan) - Hidayani, Sri; Harpiana Rahman; Septiyanti; Fairus Prihatin Idris; Haeruddin (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Nearly 800 million people experience chronic malnutrition, and 159 million children under the age of 5 are stunted. Indonesia is included in 17 countries out of 117 countries that currently have 3 nutritional problems, namely stunting (height below standard), wasting (very thin), and overweight (excess weight). To produce healthy and intelligent Indonesian children, the most important initial step to take is to fulfill children's nutrition from an early age, even while still in the womb, or what is known as the First 1000 Days of Life (HPK). This study aims to determine the effect of video media on Knowledge and Attitudes about the First 1000 Days of Life (HPK) in pregnant women. This type of research is quantitative research with a